Folding and self-assembly of biological macromolecules : (World Scientific, 2004)
This proceedings volume explores the pathways and mechanisms by which constituent residues interact and fold to yield native biological macromolecules (catalytic RNA and functional proteins), how ribosomes and other macromolecular complexes self-assemble, and relevant energetics considerations.